John Gay and the London Theatre - Winton, Calhoun (University Press of Kentucky, 1993)
The Beggar's Opera, often referred to today as the first musical comedy, was the most popular dramatic piece of the eighteenth century -- and is the work that John Gay (1685-1732) is best remembered for having written. That association of popular music and satiric lyrics has proved to be continuingly attractive, and variations on the Opera have flourished in this century: by Kurt Weill and Bertolt Brecht, by Duke Ellington, and most recently by Vaclav Havel. The original opera itself is played all over the world in amateur and professional productions.